Comparative education: status controversy and dynamics of scientific development - Zbyszko Melosik (Studia z Teorii Wychowania)
The article addresses the problem of identity and status of comparative education in contemporary science, as well as its developmental dynamics and scientific potential. In its first part, the author reconstructs the debate on the 'crisis' of comparative education and also the various avenues of its critique, especially, but not exclusively, in the context of its relationship with other (sub)disciplines. Part two focuses on the developmental dynamics of comparative education, against the background of the discussion regarding the various criteria and aspects of estimating the state of (sub)disciplines. Thus, the theoretical and methodological openness of comparative education and its responsiveness to social change will be presented. Furthermore, comparative education is placed in the context of the debate between essentialism and scientific constructivism, the problem of interdisciplinarity and research integration, the density paradox or the narcissism of small differences, as well as the challenge of postmodernism. The final section of the text presents the idea of a comparative educator as a traveller and its potential to transcend one's own epistemological script.